2012
DOI: 10.5539/jas.v4n11p51
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Heavy Metals in Fish (Hydrocynus forskahlii, Hyperopisus bebe occidentalis and Clarias gariepinus) Organs in Downstream Ogun Coastal Water, Nigeria

Abstract: In this study accumulation of some heavy metals Cadmium (Cd), Chromium (Cr), Cobalt (Co), Nickel (Ni) and Lead (Pb) in the operculum, gills, heart, kidney, muscle and vertebrae were determined in some fishes (Hydrocynus forskahlii, Hyperopisus bebe occidentalis and Clarias gariepinus) collected from fishermen around Ogun estuary. The accumulation of the metals in different organs showed significant differences (P<0.05) except lead accumulation. However, the bioaccumulation of the heavy metals was species-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…Studies carried out with different fish species have revealed that non-essential metals can produce toxic effects in fish by disturbing physiological activities [4], biochemical processes [5], reproduction and growth [6]. Among the heavy metals, Cd is one of the most toxic, nonessential heavy metal and accumulates in tissues of aquatic organisms like fish [7,8]. Problems with Cd bioaccumulation were studied by many authors in aquatic animals [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out with different fish species have revealed that non-essential metals can produce toxic effects in fish by disturbing physiological activities [4], biochemical processes [5], reproduction and growth [6]. Among the heavy metals, Cd is one of the most toxic, nonessential heavy metal and accumulates in tissues of aquatic organisms like fish [7,8]. Problems with Cd bioaccumulation were studied by many authors in aquatic animals [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Then, they were cooled, filtered, and placed in plastic bottles. Acidic digestion of the sample was done according to the procedures mentioned in [32], but the mineralization procedures were modified for the current study. The determination of heavy metals in the fish tissues was carried out using an atomic absorption spectrophotometer (Perkin-Elmer model 5000, Perkin-Elmer Corp, Waltham, MA, USA).…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…Bioaccumulation of Iron (Fe) was above FEPA and WHO limits. Murtala et al [6] detected high value at downstream Ogun coastal water and were also above the recommended limit but not as high as those recorded in the study area. Ayoola and Dansu [26] reported lower concentrations of Cadmium (Cd), Chromium (Cr), Lead (Pb) and Zinc (Zn) in Chrysichthys nigrodigitatus and Pythonichthys macrurus collected at Makoko fishing site compared to the current study; the concentrations of heavy metals in the fish samples were above WHO permissible limit.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metals are found in marine environment that occur because of pollution which is due to the discharge of untreated wastes into water bodies by industries and runoffs. [6]. Many pollutant are found in crude oil due to its geological proximity most especially heavy metals, since they play important role in biological systems, whereas mercury, lead and cadmium are toxic, even in trace amounts.…”
Section: Introductionmentioning
confidence: 99%